AN ANALYSIS OF INTERPERSONAL ATTITUDES THROUGH DORMITORY-BASED EDUCATION OF TEACHER CANDIDATES: (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract: This study investigated interpersonal attitude through dormitory-based life of PPG-SM3T participants and was conducted from March to September, 2015. It had 2 periods. Each periods lasted for 3 months. Total sampling technique was applied: 64 participants. They represented Biology, Physics, Chemistry and Economics study programs and were divided in to 5 groups. Parameters in this study covered 9 items for interpersonal attitudes. The employed data analysis was descriptive: means and percentages. The findings demonstrated that the mean score was â¥ 3,6: In the 1st period, the creative score reached 71,88% and improved to be 84,38% in the 2nd period. Discipline attitude in the 1st period was 76,56% and improved 100% in the second period. The score for courtesy in the 1st period was 84,37% and increased 100% in the 2nd period. Disciplined, courteous and creative attitudes in the 1st period need guidance. After following guidance in the 2nd period, only creative attitude need guidance. This study concludes that such guidance is effective to build interpersonal attitudes.Keywords: interpersonal attitude, Dormitory-based education, PPG-SM3T